Internalisasi Nilai-Nilai Islam Santri Bekas Molimo dalam Jamaah Telulasan - Mukhammad Handy dwi Wijaya; Septi Ariadi (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
Research related to santri and molimo has been researched from various sides and perspectives, it is interesting to study through a phenomenological approach to explore data about former molimo santri in an Islamic group located in Ngimbangan Village, Mojosari District, Mojokerto Regency. This is interesting to research because of the very unique form of the group. The research objective was to determine the form of interaction to provide socialization of Islamic values to ex-molimo santri to stay away from these taboos. The research method used a qualitative approach with a phenomenological type through participant observation, in-depth interviews, and documentation. The founder of Jamaah Telulasan had an interesting way to convert and embrace the members of the congregation or often referred to as santri in the congregation. The attitude of the congregation founders in providing internalization of Islamic values with a horizontal approach is an approach between friends and friends not between teachers and students. In the Nahdlatul Ulama tradition, educational interaction is vertical between kyai and santri, in contrast to the kyai in Jamaah Telulasan who deconstructs space that is moved horizontally. It is very interesting to study because students whose backgrounds are gambling players, thieves, adulterers, drug users, drunks change. Molimo (thief, madon, playful, drunk, mad). Suggestions for further research are to look at the habitus of ex-molimo santri in the Telulasan congregation through Peter L. Bourdieu's theory of social practice with the concepts of habitus, arena and capital theory.